Synthesis and characterization of lithium-manganese-oxide electrodes for lithium battery applications - Rossouw, Margaretha Hendrina (Department of Chemistry, 2016)
As the electronics industry moves more towards portable equipment the demand for batteries, especially rechargeable batteries, is increasing. Lithium batteries have several advantages over other competitive systems. Coupled with the inexpensive and environmentally friendly manganese dioxide, Li/MnO₂ batteries are being used extensively for powering a range of devices, but particular electronic systems.